Evaluation of the National Medical Commission-Mandated Family Adoption Programme as a community-based learning tool among second-professional MBBS students in central India: a cross-sectional study - Lilhore, Shiwani; Verma, Tinku; Chouksey, Mahendra (International Journal of Research in Medical Sciences, 2026)
Background: Community-based medical education is widely recognized as a critical approach for enabling medical students to understand social determinants of health and primary healthcare delivery. In India, NMC introduced the FAP to integrate community-oriented experiential learning into undergraduate medical education while simultaneously addressing community health needs. The main objective of the programme was to encourage medical students to actively participate in community health and well-being and to provide real-world experience in dealing with socio-economic and health-related issues. Methods: A cross-sectional descriptive study was conducted by the department of community medicine at a tertiary care medical college in central India during July 2024-September 2024. Seven villages were randomly selected under the family adoption programme. Anthropometric measurements, blood pressure assessment, hemoglobin estimation, and random blood sugar testing were performed following standard protocols. Results: Out of 200 sanctioned MBBS seats, 188 students participated in the programme. A total of 563 households comprising 3,391 individuals were covered. High blood pressure was observed in 12.9 of men and 6.9 of women and high blood sugar was observed in 3.2 of them. At the age of less than five, a quarter of the children (29.4) was found to be shorter than ought to have been, and a fifth (20.7) of the weight. The prevalence of anemia was higher in the adult population (15-49 years old) where 60.0 per cent of women and 37.0 per cent of men were afflicted. Conclusions: The family adoption programme informed numerous individuals in the society and provided the undergraduates of the medical fields with a practical learning opportunity.